The effect of an infographic promotion on research dissemination and readership: A randomized controlled trial. Issue 6 (5th October 2018) - Huang, Simon; Martin, Lynsey J.; Yeh, Calvin H.; Chin, Alvin; Murray, Heather; Sanderson, William B.; Mohindra, Rohit; Chan, Teresa M.; Thoma, Brent
Abstract : CLINICIAN'S CAPSULE : What is known about the topic? Infographics are graphical illustrations of complex ideas that are broadly shared on social media platforms. What did this study ask? What is the effect of a social media strategy using infographics on the readership and dissemination of research articles? What did this study find? Infographic articles were associated with increased Altmetric scores and abstract views, but not full-text views. Why does this study matter to clinicians? The promotion of articles with infographics may increase awareness and dissemination of research findings among clinicians. Abstract: Objective: Journals use social media to increase the awareness of their publications. Infographics show research findings in a concise and visually appealing manner, well suited for dissemination on social media platforms. We hypothesized that infographic abstracts promoted on social media would increase the dissemination and online readership of the parent research articles. Methods: Twenty-four articles were chosen from the six issues of CJEM published between July 2016 and June 2017 and randomized to infographic or control groups. All articles were disseminated through the journal's social media accounts (Twitter and Facebook). Control articles were promoted using a screen capture image of each article's abstract on the journal's social media accounts. Infographic articles were promoted similarly using a visual infographic. Infographics were also published and promoted on the CanadiEM.org's website and social media channels. Abstract views, full-text views, and the change in Altmetric score were compared between groups using unpaired two-tailed t-tests. Results: There were no significant differences in the groups at baseline. Abstract views (mean, 95% CI) were higher in the infographics (379, 287-471) than the control group (176, 136-215, p <0.001). Mean change in Altmetric scores was higher in the infographics (26, 18-34) than in the control group (3, 2-4, p <0.0001). There was no difference in full-text views between the infographics (50, 0-101) and control groups (25, 18-32). Conclusion: The promotion of CJEM articles using infographics on social media and the CanadiEM.org website increased Altmetric scores and abstract views. Infographics may have a role in increasing awareness of medical literature. Résumé: Contexte: Les responsables des revues utilisent les médias sociaux pour faire connaître leurs publications. L'infographie permet de présenter des résultats de recherche d'une manière concise et visuellement accrocheuse, moyen bien adapté à la diffusion de connaissances dans les plateformes de médias sociaux. L'étude visait donc à vérifier l'hypothèse selon laquelle la promotion infographique de résumés dans les médias sociaux aurait pour effet d'accroître la diffusion ainsi que le nombre de cyberlecteurs des articles maîtres en version intégrale. Méthode: Ont été choisis 24 articles tirés des 6 numéros de la revue Canadian Journal of Emergency Medicine (CJEM) publiés entre juillet 2016 et juin 2017, et répartis au hasard entre le groupe d'infographie et le groupe témoin. Tous les articles ont été diffusés par l'intermédiaire des comptes de médias sociaux (Twitter and Facebook) de la revue. Les articles dans le groupe témoin ont fait l'objet de promotion à l'aide d'une capture d'écran du résumé de chacun des articles dans les comptes de médias sociaux de la revue. Les articles dans le groupe d'infographie ont fait l'objet d'une promotion comparable, mais à l'aide d'une présentation visuelle assistée par ordinateur, en plus d'être publiés et promotionnés dans le site Web CanadiEM.org et les chaînes de médias sociaux. Le nombre de visionnements des résumés et des articles en version intégrale ainsi que les variations des mesures Altmetric ont aussi été comparés entre les deux groupes à l'aide de tests bilatéraux non appariés. Résultats: Au départ, il n'y avait pas de différences importantes entre les deux groupes. Toutefois, le nombre de visionnements des résumés (moyenne; IC à 95 %) était plus élevé dans le groupe d'infographie (379 : 287-471) que dans le groupe témoin (176 : 136-215; p <0, 001). Il en allait de même pour les variations moyennes des mesures Altmetric (26 : 18-34 dans le groupe d'infographie contre 3 : 2-4 dans le groupe témoin; p <0, 0001). Par contre, il n'y avait pas de différence entre les deux groupes (infographie : 50 [0-101]; témoin (25 [18-32]) pour ce qui est du nombre de visionnements des articles en version intégrale. Conclusion: La promotion des articles de la revue CJEM à l'aide de l'infographie dans les médias sociaux et le site Web CanadiEM.org s'est traduite par une augmentation des mesures Altmetric et du nombre de visionnements des résumés. L'infographie pourrait donc permettre une diffusion accrue de la documentation médicale.